Knowledge and Attitudes of Adults towards Smoking in Pregnancy: Results from the HealthStyles© 2008 Survey - Polen, Kara ND (Matern Child Health J, 2015)
OBJECTIVES: Smoking during pregnancy is causally associated with many adverse health outcomes. Quitting smoking, even late in pregnancy, improves some outcomes. Among adults in general and reproductive-aged women, we sought to understand knowledge and attitudes towards prenatal smoking and its effects on pregnancy outcomes. METHODS: Using data from the 2008 HealthStyles© survey, we assessed knowledge and attitudes about prenatal smoking and smoking cessation. We classified respondents as having high knowledge if they gave ≥5 correct responses to 6 knowledge questions regarding the health effects of prenatal smoking. We calculated frequencies of correct responses to assess knowledge about prenatal smoking and estimated relative risk (RR) to examine knowledge by demographic and lifestyle factors. RESULTS: Only 15% of all respondents and 23% of reproductive-aged women had high knowledge of the adverse effects of prenatal smoking on pregnancy outcomes. Preterm birth and low birth weight were most often recognized as adverse outcomes associated with prenatal smoking. Nearly 70% of reproductive-aged women smokers reported they would quit smoking if they became pregnant without any specific reasons from their doctor. Few respondents recognized the benefits of quitting smoking after the first trimester of pregnancy. CONCLUSIONS: Our results suggest that many women lack knowledge regarding the increased risks for adverse outcomes associated with prenatal smoking. Healthcare providers should follow the recommendations provided by the American Congress of Obstetricians and Gynecologists, which include educating women about the health risks of prenatal smoking and the benefits of quitting. Healthcare providers should emphasize quitting smoking even after the first trimester of pregnancy.